Potret Self-system Remaja dengan Perilaku Tindakan Seksual Berisiko di Provinsi Jambi - Sunardi, Kartika Setyaningsih; Martha, Evi; Guspaneza, Essi (Jurnal Promosi Kesehatan Indonesia, 2020)
Background: Indonesia's largest population group is adolescents. Adolescents have a critical period in the human life cycle and put adolescents vulnerable to the influence of sexual risky behavior. The purpose of this study was to describe the self-portrait system that causes the sexual risky behavior of adolescents in Jambi Province.Method: This was quantitative research using a cross-sectional design. As much as 661 unmarried male and female adolescents (15-24 years) in Jambi Province involved as the sample of the 2017 IDHS. Data were analyzed using univariate, bivariate, and multivariate analysis.Results: The result showed 68.1% of adolescents performed sexual risky behavior in Jambi Province. The Self-System Factors associated with sexual risky behavior of adolescents were age, knowledge, attitude, and alcohol consumption. The probability of adolescents in the age group of 20-24 years, who have low knowledge, negative attitudes, and consumed alcohol will perform sexual risky behavior of 95.78%. The result of the multivariate analysis found that the most influential variable with sexual risky behavior in adolescents was the attitude. It is suggested to the Department of Health and BKKBN to increase sexual knowledge about reproductive health and sexuality to adolescents.